2002
DOI: 10.1289/ehp.02110s3441
|View full text |Cite
|
Sign up to set email alerts
|

Birth defects, season of conception, and sex of children born to pesticide applicators living in the Red River Valley of Minnesota, USA.

Abstract: We previously demonstrated that the frequency of birth defects among children of residents of the Red River Valley (RRV), Minnesota, USA, was significantly higher than in other major agricultural regions of the state during the years 1989-1991, with children born to male pesticide applicators having the highest risk. The present, smaller cross-sectional study of 695 families and 1,532 children, conducted during 1997-1998, provides a more detailed examination of reproductive health outcomes in farm families asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(136 citation statements)
references
References 63 publications
6
119
0
7
Order By: Relevance
“…Birth rates with urogenital abnormalities, as well as abnormalities in other systems, were significantly increased in highuse areas. Another study [74] also suggested a possible gene-environment interaction at work in this agricultural region. A total of 22% of the families in which the father applied the herbicides had more than one child with a birth defect.…”
Section: Ii-1 Arguments For An Environmental Contributionmentioning
confidence: 88%
“…Birth rates with urogenital abnormalities, as well as abnormalities in other systems, were significantly increased in highuse areas. Another study [74] also suggested a possible gene-environment interaction at work in this agricultural region. A total of 22% of the families in which the father applied the herbicides had more than one child with a birth defect.…”
Section: Ii-1 Arguments For An Environmental Contributionmentioning
confidence: 88%
“…In two studies on organochlorine pesticide exposure that were performed in the United States [22] and Spain [19], long-term breastfeeding was found to be protective against poorer psychomotor development as assessed on Bayley Scales of Infant Development. Recently, Garry et al (2002) [25] in a follow-up of children born to applicators of the fumigant phosphine and/or herbicide glyphosate found that these children were more likely to display adverse neurological and neurobehavioral developmental effects: attention defi cit disorder (ADD), attention-defi cit hyperactivity disorder (ADHD), or autism [25].…”
Section: Transient Effect Of Exposure Associated With Agementioning
confidence: 99%
“…In addition, the Fenton method has the advantage that both non-polar compounds can be degraded by OH radicals and rendered "harmless" and that stable polar compounds can be removed by the adsorption on Fenton sludge. Thus, for example, non-polar phosphorus compounds that are not removed by the Fe III method can also be transformed into inorganic phosphate, which is then discharged as insoluble FePO 4 with the Fenton sludge. In Table 2, the NIT, RIT and LBT are compared in terms of time, effort and sensitivity of the bacteria.…”
Section: Experiments Regarding Fenton Methods (Fe II /H 2 O 2 )mentioning
confidence: 99%
“…PPA can be classified according to their mode of action, substance class and application. Insecticides (mainly halogenated hydrocarbons, pyrethroids, phosphoric acid esters and carbamates), herbicides (mainly phenoxycarboxylic acids, heterocyclic compounds, phosphonates) and fungicides (often organometallic compounds) are of the greatest importance worldwide [4].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation